An analysis of private investors' stock market return forecasts - Erik Theissen (University of Cologne, Centre for Financial Research (CFR), 2005)
We analyze data on stock index forecasts made by private investors. The implied returns calculated from these forecasts exhibit negative skewness and excess kurtosis. Past returns have a positive impact on the implied returns, consistent with investors expecting positive momentum. Females are less optimistic than males, but their forecasts have higher standard deviation. Consistent with the weekend effect, implied returns from estimates entered on weekends are significantly lower than those entered on weekdays. Implied returns are not consistently related to the weather conditions on the day the forecast was made.
Keywords: G14; 330; Behavioral Finance; Weekend effect; Weather effect